Match load & technique differences in winning and losing female youth tennis players on clay courts - Khamros, Watunyou; Chinnasee, Chamnan; Pongsiri, Tatpicha; Chaiyapade, Weerapong; Rattanasateankij, Worrawit; Sangkaew, Teeraphan (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The aim of the study was to analyse the differences in match load and technique between winners and losers in female youth tennis competitions on clay courts. Ten female youth tennis players (age 15.80 ± 0.42 years), all ranked in the singles ranking in International Tennis Federation (ITF) Junior. A simulated clay court competition using standard rules was the setting for the study. Technical data was scrutinized using Dartfish and the matched load was evaluated and contrasted by utilizing Banister's, Edward's, and Rating of Perceived Exertion–based Training Impulse (RPE TRIMP). The results found that the second set has a statistically significant lower load than the first set up p ≤ .05. Pearson correlation indicated that the Backhand and Smash Technique has a strong relationship with training impulse (TRIMP) in all winners, but mostly TRIMP tends to have a negative relationship with many techniques in the losers group. It appears that winning youth players have lower competition loads than losing players and are more efficient in their technique in competition. The importance of proper match load analysis and competition technique together may be a guideline to increase the chance of winning in youth tennis competitions on clay courts.